Distribution and Antibiotic Resistance Analysis of 13,048 Clinically Common Isolates - Zhao J; Yue P; Li ZJ; Xu T; Xing GZ; Shao Y; Yu HY (Infection and Drug Resistance)
Jing Zhao,1,* Peng Yue,2,* Zhi-jie Li,3,* Ting Xu,1 Guo-zheng Xing,1 Yan Shao,1 Hong-yuan Yu1 1Department of Clinical Laboratory, Beijing Aerospace General Hospital, Beijing, People’s Republic of China; 2Northern Medical Branch of PLA General Hospital, Haidian, Beijing, 100080, People’s Republic of China; 3Obstetrics and Gynecology, Beijing Aerospace General Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hong-yuan Yu, Email 13051839088@163.comObjective: This study investigated the distribution and antibiotic resistance profiles of common bacteria isolated from clinical specimens at a hospital’s microbiology laboratory between 2020 and 2022.Methods: A retrospective analysis was conducted on microbial culture results from clinical specimens collected over three years, including sample types, departmental distribution, pathogen species, and resistance profiles.Results: A total of 13,048 unique pathogenic strains were isolated, predominantly from respiratory and urine specimens. Secretion specimens exhibited the highest positive detection rate (73.6%), while blood specimens showed a lower rate (9.7%). The five most frequently isolated pathogens were: Klebsiella pneumoniae (K. pneumoniae) (19.6%), Pseudomonas aeruginosa (P. aeruginosa) (14.7%), Escherichia coli (E. coli) (9.2%), Acinetobacter baumannii (A. baumannii) (8.0%), and Candida albicans (C. albicans) (7.0%). Gram-negative bacteria constituted 53.7% of all isolates (7009/13,048). A total of 7590 multidrug-resistant organisms (MDRO) were identified, corresponding to a detection rate of 21.3% (7590/35,613). The detection rates of carbapenem-resistant Enterobacteriaceae (CRE) increased annually: 7.2% (2020), 8.6% (2021), and 14.4% (2022).Conclusion: The annual detection rate of CRE increased during the study period, while the rate of methicillin-resistant Staphylococcus aureus (MRSA) declined. Timely and effective interventions targeting pathogenic bacteria are essential for controlling and mitigating nosocomial infection risks.Keywords: multidrug-resistant organisms, monitoring, hospital infection, prevention and control, CRE